Myanmar/Burma inside challenges, outside interests - Rieffel, Alexis 1941- (Brookings Institution Press, 2010)
Through the eyes of ASEAN members, neighbors China and India, and the United States, examines current state of affairs in Myanmar/Burma and focuses on national reconciliation and economic development, as the country approaches multiparty elections in fall 2010 and after the Obama presidency has initiated a new approach to relations"--Provided by publisher.